Determinants of Capital Structure in the South African Listed Property Sector - Calvosa, Alessandro (Department of Finance and Tax, 2021)
The purpose of this study is to investigate whether empirical evidence support traditional determinants and theories of capital structure in the listed South African property industry, a relatively new adopter of the globally recognised and regulated Real Estate Investment Trust (REIT) structure. There currently exists little academic literature focusing on this specific topic in the South African property sector. Furthermore, the recent change of the prevalent legal form of South African listed property companies, affords a unique opportunity to investigate the possible impact of regulatory changes on capital structure within this context. A panel regression is applied to a sample of 39 firms over the period 2005 to 2019, which includes all property companies with South African exposure listed on the JSE, both during the pre-REIT and REIT regimes. This results in an unbalanced panel of 314 company years. The regime change to the REIT structure appears to have, on average, increased the use of leverage in South Africa's listed property sector. Debt usage, however, remains well below the allowed regulatory limit and lower than worldwide counterparts. The regression results offer support for the trade-off theory, pecking order theory and market timing theory in the South African listed property context, and are generally in agreement with international findings. Thus, size is found to be positively correlated to debt levels, in line with trade-off theory prediction. Growth opportunities tend to increase leverage ratios, which is consistent with the pecking order theory. Evidence for market timing behavior is the positive correlation found between 12-month share price movements and leverage. Other firm specific determinants including share volatility and interest cover ratio also offered pecking order theory support. Inflation was also found to have a significant effect on leverage in the sector. In conclusion, it is found that the evidence supports elements of most capital structure theories in the South African listed property sector.